A Dual PI3K/HDAC Inhibitor Downregulates Oncogenic Pathways in Hematologic Tumors In Vitro and In Vivo - Yan, Zheng; Zhang, Kehui; Ji, Ming; Xu, Heng; Chen, Xiaoguang (Frontiers in Pharmacology, 2021)
Purpose: To investigate the efficacy and mechanism of compound 23, a PI3K/HDAC dual-target inhibitor, on hematologic tumor cells in vitro and in vivo. Methods: MTS Kit was used to study the antiproliferative effects in vitro. Western blot was used to analyze the involved signaling pathways. Flow cytometry was used to analyze apoptosis and cell cycle. The antiproliferative effects were evaluated in vivo using EL4 and A20 xenograft models. The CCLE database was used to analyze gene expression. Results: Compound 23 significantly inhibited the proliferation of hematologic tumors; it simultaneously regulated PI3K/HDAC pathways and induced apoptosis and G1-phase arrest in EL4, NB4, and A20 cells in vitro. When tested in vivo, compound 23 significantly inhibited the proliferation of EL4 and A20. The expression levels of ErbB2 and ErbB3 decreased in hematologic tumors compared with it in solid tumors. Conclusion: Compound 23 modulates the PI3K/HDAC pathway, which results in significant inhibition of hematologic tumor proliferation in vivo and in vitro. The differential levels of ERBB2 and ERBB3 might be related to the difference in the effect of compound 23 on hematologic tumors and solid tumors.